Kinematic characteristics of the movement technique of highly qualified biathletes - Zagurskiy N.S.; Makhambetov T.Zh.; Romanova Ya.S. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the features of the use of tactical techniques and differences in the kinematic parameters of the movement technique of biathletes with a simultaneous two-step skating move and a simultaneous one-step skating move in conditions of competitive activity. Methods and structure of the study. The article examines the kinematic and dynamic indicators when moving with simultaneous two-step and simultaneous one-step skating moves (ODKH and OOKH) of highly qualified biathletes during the races of the Russian Championship 2023 in Khanty-Mansiysk. Results and conclusions. The analysis made it possible to establish that leaders, when covering a competitive distance, change the ratio of the length and frequency of steps and the amount of effort when pushing off. The first lap of the distance is overcome by climbing with great rolling and a relatively low frequency of movements, the second lap is completed by increasing the frequency of the cycle and minimizing effort. On the third circle, an increase in speed is achieved by increasing the cycle frequency and cycle length relative to the 2nd circle. For athletes who did not make it into the top ten of the final protocol, the limiting factor in maintaining a high speed of completing a distance with a simultaneous one-step skating stroke is power potential.